Economic Regional Dynamics in Argentina during Import Substitution Industrialization: a Comparative Analysis (1914 - 1959) - Talassino, Mauricio Rodrigo (2024)
Fil: Talassino, Mauricio Rodrigo. Universidad de San Andrés. Departamento de Economía; Argentina.